Reducing English-Speaking Anxiety in ESP Contexts through Flipped Learning: Evidence from Informatics Engineering Students - ANINDHIASTI ASRI (English Department, Faculty of Humanities, Udayana University, 2026)
This study investigates the extent to which flipped learning reduces English-speaking anxiety among Informatics Engineering students. Many students in technical disciplines struggle to communicate effectively in English due to limited proficiency, low confidence, and heightened speaking anxiety, which can impede active participation and academic performance. A mixed-methods approach was employed, combining a quasi-experimental one-group pretest–posttest design with a post-intervention perception survey and classroom observations. The study involved 25 second-year students at Universitas Duta Bangsa Surakarta. A 10-item speaking-anxiety questionnaire adapted from the Foreign Language Classroom Anxiety Scale was administered before and after four flipped-classroom sessions, alongside a 7-item perception survey. Quantitative analysis using a paired-samples t-test revealed a statistically significant decrease in speaking anxiety (pretest M = 3.86, SD = 0.28; posttest M = 3.40, SD = 0.25; t(24) = -5.27, p < .01). Reductions were observed across all measured anxiety dimensions, particularly in classroom participation and presentation-related tension. Qualitative responses further indicated increased confidence and perceived preparedness. The findings suggest that flipped learning may serve as a pedagogical approach to alleviating speaking anxiety and strengthening technical English communication in ESP contexts.